ANALISA VARIASI BEBAN PENDINGIN UDARA KAPASITAS 1 PK PADA RUANG INSTALASI UJI DENGAN PEMBEBANAN LAMPU - ., Mustaqim; ., Rusnoto; Subedjo, Slamet (ENGINEERING, 2011)
Faculty Of Technique, University Pancasakti Non irigated dry field. This Research aim to to  know air cooler burden variation influence to prstasi work cooler machine ( AC) 1PK. This research its nucleus;core do with its it lamp burden test installation space will have an effect on to achievement coefficient This research use installation space test and appliance test that is column cooler machine ( AC) 1 PK which consist of  compresor, ekspansi kondensor,katup, and evaporator by using R 22. To make burden variation , in test space attached lamp which its burden variation of 100 watt, 200 watt, 600 watt. From done/conducted by research is menunjukan that is ever greater of given burden, hence done/conducted by job/activity is ever greater kompresor. With the level of done/conducted by job/activity is kompresor , yielded achievement coefficient progressively mount. burden 100 watt, 400 watt, 600 watt alternately yielded COP 16,51438, 17,83301, and 21, 2554, while required time in course of refrigeration column until temperature 18? progressively increase. Keyword: Machine Cooler, Burden Lamp, R-22, Kompresor, COP